The Family and Social Change in the Newfoundland Outport - Davis, Dona (Culture, 1983)
Studies of the changing outport family have emphasized the role of modern fishing technology in undermining the traditional patrilocal extended family and have overlooked the tenacity of traditional family values, identification with the fishery and sense of community in everyday life. This paper focuses on a southwest coastal outport village and describes the variety of women’s attitudes towards family concerns such as courtship and marriage, birth control, child-rearing, male and female work roles. Cultural continuity and the integrity of the family have been maintained through the mechanisms of strong female networks, a powerful egalitarian ethic, and pride in the past.